Fiscal Discrimination Between Consumer Groups: Tax Burden Distribution Under Price Discrimination - Jörg Plewka (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
In this paper it is analysed, how, under price discrimination, the tax burden is shared between the distinct consumer groups. Unit and ad valorem taxes are compared, revealing an impossibility of fiscal discrimination with regard to price changes. Contrary to conventional tax incidence analysis, it is shown that quantities traded do matter. Relative market shares are decisive for the distribution of tax burdens thereby opening up an opportunity for fiscal discrimination in choosing tax types. This discriminatory potential is limited and not caused by price discrimination per se but rather due to monopolistic supply.
Keywords: H22; L11; 330; Tax incidence; unit tax; ad valorem tax; price discrimination; Umsatzsteuer; Verbrauchsteuer; Steuerinzidenz; Preisdifferenzierung; Theorie